ANALYSIS OF THE DEFORMITY'S OF KNEE AND OF Q ANGLE IN INDIVIDUAL'S CARRIERS OF CHONDROMALACIA PATELLAR. (Fiep Bulletin - online, 2014)
The proposal of this study was to analysis the correlation of the deformity's postural of knee and of “Q” angle with chondromalacia patellar in individual's carriers of chondromalacia patellar. The research was carried through in the sector of physiotherapy of the clinics in study in the period of February to May. Twenty-eight (28) individuals where analyzed that they possessed the diagnostic of chondromalacia patellar. Of these, 61% of feminine sex and 39% of the masculine sex, with average age of 28 years. An evaluation was performed, which was anamneses and physical examination, where this test consisted of Waldron, postural deformities evaluation of the knees and measure the angle "Q". For the analysis of the data was used to test non parametric Fisher's Exact. By making the correlation of test Waldron with chondromalacia patellar, that presented significance (p = 0,039). The same happened in pain retropatelar correlation with chondromalacia (p